Impact of gypsum type on the setting and hardening performance and mechanism of water-rich filling materials - LIU Juan-hong; MA Yi; WANG Zu-qi; GAO Meng; ZHOU Qian (工程科学学报)
As for the problem that different gypsum types have different influence on the condensation performance of water-rich filling materials,micro experiments,such as X-ray diffraction,scanning electron microscopy and infrared spectroscopy,were used to analyze the composition of the hardened body and investigate the influence of dihydrate gypsum and hemihydrate gypsum on the setting and hardening characteristics of water-rich filling materials. It is found that in a water-rich filling material system of sulphoaluminate cement-gypsum-lime,the gypsum type should be dihydrate gypsum so as to ensure the normal condensation setting and hardening; if hemihydrate gypsum is used as a raw material,the water-rich filling material has not strength after hydrating for 7 d. When dihydrate gypsum is adequate,the generated ettringite crystals are fine needle-like; but when dihydrate gypsum is inadequate,the generated ettringite crystals are short hexagonal columnar. The strength of the water-rich filling material is mainly derived from ettringite generated by the reaction of sulphoaluminate cement gypsum and lime,rather than the hydration products of cement generated by itself such as hydration calcium sulphoaluminate,alumina gel and calcium hydroxide.